Persepsi Review Produk Make Up Melalui Beauty di Vlogger Youtube - Nur Maghfirah Aesthetika; Nur Tita Kusdiyanti (Universitas Muhammadiyah Sidoarjo, 2020)
Youtube is a very popular media by the people in Indonesia, especially the makeup artist. According to data from Wearesocial, Youtube has occupied the first position with a percentage of approximately 88%, and then followed by a second position and so on by Facebook, Whatsapp, and Instagram. Yotube itself is about entertainment, Video clips, or Vlog (Video Blog) where the vlogs can contain about private vacation videos, promote goods or products, or daily activities in this research using video blogs From Tasya Farasya entitled